(untitled) (Al-Academy, 2023)
Theater is described as a form of human expression, and an important human necessity, through which the needs of individuals and societies are expressed, and an important mediator for the transfer of educational, social and intellectual dimensions. Hence, the importance of the child’s theater emerged as a guiding educational method that affects the child’s development educationally, emotionally, psychologically and socially through imaginative play that combines enjoyment and entertainment. The grotesque is one of the artistic methods that work to attract the attention of the recipient in theatrical texts that combine dissonance and contradiction in a dramatic act that combines the beautiful and the ugly, the honest and the false together as an expressive method for the theatrical text directed to the child. The first chapter (the methodological framework) dealt with the research problem that was identified in the following axis: What are the works of grotesques in children’s theater texts? The importance of research on the subject of grotesques is evident as it is a sensor that provides researchers and stakeholders in the field of children’s theater by shedding light on the concept of grotesques and its activities in his book the theatrical text directed to the child. Child . The researcher reached the most important results: 1-Presenting what is positive and negative in an objective manner within the drama of the theatrical text 2-The presence of animal and plant characters, which makes the text a kind of humanized plays